Influence of high‐altitude grazing on bone metabolism of growing sheep. Issue 1 (13th October 2011) - Liesegang, A.; Hüttenmoser, D.; Risteli, J.; Leiber, F.; Kreuzer, M.; Wanner, M.
Summary The objective of this study was to identify the effect of high alpine grazing, associated with varying pasture grass qualities and more pronounced exercise on typically steep slopes, on bone metabolism by improving bone density and enhancing bone turnover in growing sheep. Twenty‐four 5‐month‐old sheep were randomly assigned to two groups. One group was kept at high altitude (HA; 2000–2200 m a.s.l.) for 3 months, and the other group (C; control) remained in the lowlands (400 m a.s.l.). Both groups were kept in grazing pastures with access to good‐quality swards. Before the start of the experiment, blood samples were taken, the sheep were weighed, and the left metatarsus of each animal was analysed by quantitative computer tomography. After 1 month, blood samples were taken and body weight was measured, followed by biweekly sampling. Finally, the animals were slaughtered, and the bones were collected for analysis of various bone parameters. Body weight development did not differ between the groups. Concentrations of 25‐OH‐Vitamin D, carboxy‐terminal telopeptide of type I collagen and activities of bone‐specific alkaline phosphatase were always higher in the HA group than in the C group, except on the last two sampling dates. Bone mineral content and density increased in both groups during the experiment, but more intensively in the HA group. In addition, the cortical thickness of the HA group increased. The present study demonstrates an increase in bone turnover and mineral content of the bones of the growing sheep grazing in high alpine pastures. The factors associated with HA grazing, therefore, clearly seem to improve bone composition.